2017
DOI: 10.1111/jwas.12471
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Artificial Light Technologies for Indoor Aquaponic Production of Swiss Chard, Beta vulgaris, and Kale, Brassica oleracea

Abstract: To date, most aquaponic research has been conducted outdoors in tropical climates or in greenhouses in subtropical climates. For more northerly latitudes, aquaponic production will require supplemental light in greenhouses or insulated buildings. Two separate 3-wk growth trials were conducted to evaluate the effects of four different lighting technologies on the growth of Swiss chard, Beta vulgaris (Trial 1) and kale, Brassica oleracea (Trial 2) in aquaponic systems. Light technologies evaluated included fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…Differences in Trial 2 with basil were even larger, with LED producing 152% more plant weight per unit energy than IND, 219% more than MH, and 234% more than FLO. These results are in agreement with those of Oliver et al (2018) for both Swiss chard ( Beta vulgaris ) and kale ( Brassica oleracea ). The economic impacts of these efficiencies will vary according to the electric power costs in the region of production.…”
Section: Discussionsupporting
confidence: 93%
“…Differences in Trial 2 with basil were even larger, with LED producing 152% more plant weight per unit energy than IND, 219% more than MH, and 234% more than FLO. These results are in agreement with those of Oliver et al (2018) for both Swiss chard ( Beta vulgaris ) and kale ( Brassica oleracea ). The economic impacts of these efficiencies will vary according to the electric power costs in the region of production.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that different light sources can alter the metabolite status in plant bodies (Fukuda, 2019). LED lights are known to have some advantages such as adjustability of the light spectrum, small size, long-lasting, low heat effects to the ambient for plants (Lin et al, 2013;Oliver et al, 2018). At the same time, it has been shown in studies that LED lights can achieve the same efficiency by consuming 75% less energy compared to light sources such as Metal Halide (Singh et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This section describes plant growing environments [44], hydroponic systems [45], and lighting sources [46] that make up the horticulture unit [1]. Each of these components impact the types of plants that can be grown, the level of crop protection from pests and weather, startup cost and operational expenses.…”
Section: Horticulture Unitmentioning
confidence: 99%
“…Indoor environments provide increased temperature control but are dependent on artificial light for plant growth and electrical usage can be seven times higher than in a greenhouse [29]. Studies comparing grow light technologies demonstrated that plants grown under LED lighting tend to achieve greater production biomass under the same conditions than other artificial lights and do so with lower energy consumption [46]. However, Nelson and Bugbee [50] found that the initial expense of obtaining the LED light fixtures compared to the industry standard high-pressure sodium (HPS) fixtures made the return on investment (ROI) of LED grow lights between 5 and 10 years.…”
Section: Horticulture Unitmentioning
confidence: 99%